THE IMPLEMENTATION OF JIGSAW COOPERATIVE LEARNING IN TEACHING ENGLISH READING COMPREHENSION - Nur Shafira Khoirun Nisa; Abdul Kodir Al-Baekani; Acep Bahrum Kamil (Esteem Journal of English Education Study Programme, 2025)
This research investigated the impact of Jigsaw Cooperative Learning on improving reading comprehension among Grade VIII EFL learners in Karawang, West Java, Indonesia. Adopting a Classroom Action Research (CAR) framework grounded in Kemmis and McTaggart’s model, the study involved 44 students and utilized structured observation checklists alongside semi-structured interviews to gather data. The findings demonstrated that the Jigsaw approach significantly enhanced students’ reading comprehension by fostering expert group collaboration and joint text interpretation. Learners exhibited heightened engagement, more active participation, and a generally favorable attitude toward the instructional strategy. This study offers a valuable contribution to the field of EFL instruction, particularly in the domains of cooperative learning and curriculum design. Moreover, by employing a qualitative lens, it addresses a notable gap in the predominantly quantitative literature, offering deeper insights into the interactive and social dimensions of collaborative learning within Indonesian EFL classrooms.